Effectivity of Manure at Various Dose Added Agrobost to The Growth of Mango Seedlings - Musadia Afa; Robiatul Adawiyah (Universitas Sembilanbelas November Kolaka, 2018)
One of the efforts to increase mango production in Southeast Sulawesi is to produce high quality and high quantity mango seeds. Manure contains macro and micro nutrients that are important for plant growth and development as well as play a role in maintaining nutrient balance in the soil to improve soil properties. The aim of this study was to obtain the best manure doses applied with agrobost in improving the growth of Arumanis mango seedlings. This research was conducted in Kemaraya Sub-District of West Kendari District, Kendari City. The study design used was a randomized block design (RBD) with 6 treatments, namely: control (T0), 100 g (T1); 150 g (T2); 200 g (T3); 250 g (T4); and 300 g (T5) of manure per polybag. Each treatment was added with agrobost of 17 ml/polybag and replicated 5 times. The variables observed were plant height, stem diameter; number of leaves, and leaf area, at ages 1, 2, and 3 months after planting. The results showed that the manure added agrobost influenced the growth of Arumanis mango seedlings. The manure treatment with a dose of 150 g per polybag (T2) was the best treatment in improving the growth of Arumanis mangoes at 1, 2 and 3 months after planting. This was indicated by the plant height of 28,40; 30,94; and 32,82 cm, stem diameter of 0,44; 0,70; and 0,99 cm; and number of leaves 6,60; 7,20 and 9,00 strands were significantly higher compared to other treatments during the study